ULCERS OR INFECTIONS OF THE LOWER LIMBS IN PEOPLE WITH DIABETES MELLITUS: NURSES' KNOWLEDGE AND PRACTICES - Patrícia Helena Gonçalves; Amábile Giulia Faraoni Cardoso; Thalita da Silva Ribeiro; Silvia Matumoto; Tauani Zampieri Fermino; Cinira Magali Fortuna; Angelina Lettiere-Viana (Universidade Federal do Paraná, 2024)
Objective: To identify nurses' knowledge and practices related to lower limb ulcers or infections in people with diabetes mellitus. Method: A qualitative study was conducted with 24 nurses from family health teams in a municipality in the countryside of the State of Minas Gerais - Brazil. Semi-structured interviews were conducted in October and November 2022, analyzed using the thematic analysis technique, and discussed using the literature on the subject. Results: The study's findings revealed two crucial thematic categories: "Knowledge about lower limb ulcers or infections in people with diabetes mellitus" and "The work of nurses in caring for people with diabetes mellitus". These findings underscore the urgent need to improve knowledge and practices about ulcers or infections in the lower limbs, emphasizing the pivotal role of nurses in this process. Conclusion: The study showed that knowledge and practices about ulcers or infections in the lower limbs are fragile, highlighting the need to build knowledge in the nursing field and encourage the adoption of preventive measures by health professionals, especially primary care nurses.